The role of metabolites under the influence of genes and lifestyles in bone density changes - Lv, Xuewei; Jiang, Yanfeng; Yang, Dantong; Zhu, Chengkai; Yuan, Huangbo; Yuan, Ziyu; Suo, Chen; Chen, Xingdong; Xu, Kelin (Frontiers in Nutrition, 2022)
Purpose: Osteoporosis is a complex bone disease influenced by numerous factors. Previous studies have found that some metabolites are related to bone mineral density. However, the associations between metabolites and bone mineral density under the influence of genes and lifestyle have not been fully investigated. Methods: We analyzed the effect of metabolites on bone mineral density under the synergistic effect of genes and lifestyle, using the data of 797 participants aged 55-65 years from the Taizhou Imaging Study. The cumulative sum method was used to calculate the polygenic risk score of SNPs, and the healthful plant-based diet index was used to summarize food intake. The effect of metabolites on bone mineral density changes under the influence of genes and lifestyle was analyzed through interaction analysis and mediation analysis. Results: Nineteen metabolites were found significantly different in the osteoporosis, osteopenia, and normal bone mineral density groups. We found two high-density lipoprotein subfractions were positively associated with osteopenia, and six very-low-density lipoprotein subfractions were negatively associated with osteopenia or osteoporosis after adjusting for lifestyles and genetic factors. Tea drinking habits, alcohol consumption, smoking, and polygenic risk score changed bone mineral density by affecting metabolites. Conclusions: With the increased level of high-density lipoprotein subfractions, the risk of bone loss in the population will increase; The risk of bone loss decreases with the increased level of very-low-density lipoprotein subfractions. Genetic factors and lifestyles can modify the effects of metabolites on bone mineral density. Our results show evidence for the precise prevention of osteoporosis.